2015
DOI: 10.1186/s12871-015-0138-1
|View full text |Cite
|
Sign up to set email alerts
|

Misplacement of left-sided double-lumen tubes into the right mainstem bronchus: incidence, risk factors and blind repositioning techniques

Abstract: BackgroundDouble-lumen endobronchial tubes (DLTs) are commonly advanced into the mainstem bronchus either blindly or by fiberoptic bronchoscopic guidance. However, blind advancement may result in misplacement of left-sided DLTs into the right bronchus. Therefore, incidence, risk factors, and blind repositioning techniques for right bronchial misplacement of left-sided DLTs were investigated.MethodsThis was an observational cohort study performed on the data depository consecutively collected from patients who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 16 publications
0
27
2
Order By: Relevance
“…[37] The risk factors included women, short stature, narrow tracheal and bronchial diameter, and small DLT. A previous study showed that the McGrath Series 5 increased the incidence of DLT malposition.…”
Section: Discussionmentioning
confidence: 99%
“…[37] The risk factors included women, short stature, narrow tracheal and bronchial diameter, and small DLT. A previous study showed that the McGrath Series 5 increased the incidence of DLT malposition.…”
Section: Discussionmentioning
confidence: 99%
“…Two investigators (SY, S-HM) measured the inner diameters of the left and right mainstem bronchi on the preoperative computed tomography. [1619] The DLT size was selected based on the left bronchial diameter or sex and height of the patient. [4, 5, 16, 19]…”
Section: Methodsmentioning
confidence: 99%
“…A previous retrospective study suggested that the left-sided DLT with an obtuse tip angle was more likely to enter the right bronchus probably because the curved tip may not reach the left bronchial opening even after left rotation of the DLT. [16] We thus performed a prospective randomized trial comparing the right bronchial misplacement of left-sided DLTs with different tip angles. Our hypothesis was that the DLT with an acute tip angle enters the right bronchus less frequently than the tube with an obtuse tip angle.…”
Section: Introductionmentioning
confidence: 99%
“…Blind insertion of a DLT is a common technique; however, misplacement of a left DLT in the right mainstem bronchus was reported in 48 (4.2%) of 1,135 consecutive patients in a single centre study. 2 Subsequent manipulations of DLTs are another risk factor for tracheal trauma. 3 It is the authors' opinion that moving a DLT while the patient is in the lateral decubitus position is more difficult and traumatic and we suspect that was the mechanism of the injury described here.…”
Section: To the Editormentioning
confidence: 99%